Analysis of landslide risk in south OKU Regency, Indonesia - Hafiza Ellin; Utomo Budi; Seftinar Helfa (Glasnik Srpskog Geografskog Društva, 2024)
Landslides cause significant economic, physical, and environmental losses. This research aims to analyse landslide risk using hazard analysis, vulnerability analysis, regional capacity analysis, and landslide disaster risk analysis. The study was conducted in South OKU Regency, one of the regencies in South Sumatra Province, which frequently experiences landslides. The method used in this research is a survey method. The data includes DEM data, slope types, land cover type maps, rainfall maps, soil type maps, physical infrastructure, economic losses, environmental damage, development plans, regional capacity index, and data from structured interviews with 19 sub-district heads. Landslide analysis uses the weighting and overlay method; vulnerability analysis uses Multi-Criteria Decision Analysis; capacity analysis refers to the Hyogo Framework for Actions; and risk analysis is based on Perka BNPB No. 2 of 2012. The results of the analysis show that the landslide hazard in South OKU Regency is high and spread across more than half of the sub-districts. This landslide hazard is very vulnerable to the condition of vital physical infrastructure, has the potential to cause significant economic losses, and can damage environmental conditions. On the other hand, regional capacity in dealing with landslide danger is categorized as moderate. The risk of landslides in South OKU Regency is in the medium disaster risk class. Therefore, it is necessary to strengthen community capacity and increase preparedness in facing landslide disasters to minimize the risks posed.